The impact of appetite-regulating neuropeptide leptin on alcohol use, alcohol craving and addictive behavior: a systematic review of preclinical and clinical data - Bach, Patrick; Koopmann, Anne; Kiefer, Falk (Alcohol and alcoholism, 2021)
The appetite regulating hormone leptin, which is mainly secreted from adipose tissue, is an important regulator of food intake and modulator of reward-driven behavior. Leptin exerts its biological actions via binding to the leptin receptor, which is expressed in the hypothalamus, but also in the hippocampus, the amygdala and the substantia nigra. In the ventral tegmental area (VTA), leptin attenuates the firing rate of dopaminergic neurons that project to the Nucleus accumbens (NAc), which serves as relay to other brain areas of the “addiction network”, such as the prefrontal cortex. This suggests that leptin plays a role in the processing of rewards in the context of substance use disorders such as alcohol use disorder, especially through attenuation of dopaminergic activity in the mesolimbic reward system. This supports the plausibility of leptin’s potential effects in alcohol use disorder.We searched MEDLINE from 1990 to February 2020. All abstracts were screened for relevance and we only included publications reporting original data with a full text available in English language. Studies that did not report leptin-data, reviews or case reports/series were not included.We identified a total of N=293 studies of whom a total of N=55 preclinical and clinical studies met the specified criteria. N=40 studies investigated the effects of alcohol on leptin plasma levels, N=9 studies investigated the effects of leptin on alcohol craving and N=6 studies investigated the effects of leptin on relapse and alcohol consumption.In this review of preclinical and clinical data, we assess the role of leptin in alcohol use and the development and maintenance of an alcohol use disorder, alcohol craving and relapse. Integrating the existing preclinical and clinical data on leptin may reveal new and innovative targets for the treatment of substance use disorders in the future.